2014
DOI: 10.4331/wjbc.v5.i3.269
|View full text |Cite
|
Sign up to set email alerts
|

Can short-term fasting protect against doxorubicin-induced cardiotoxicity?

Abstract: a potential strategy to prevent Dox-induced cardiotoxicity. Future research should aim to determine the optimal regimen of fasting, confirmation that this regimen does not interfere with the antitumor properties of Dox, as well as the underlying mechanisms exerting the cardioprotective effects.© 2014 Baishideng Publishing Group Inc. All rights reserved.Key words: Fasting; Doxorubicin; Cardiotoxicity; Cardioprotection Core tip: Doxorubicin (Dox)-induced cardiotoxicity remains a significant cause of morbidity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The usefulness of STS has also been demonstrated for its attenuating properties on chemotherapy side effects. Indeed, its cardioprotective properties have been recently demonstrated during doxorubicin-based treatments (Dirks-Naylor et al 2014). In addition, a recent work on murine models revealed that following a prolonged fasting of 48-60 h prior to the administration of a high dose of etoposide, the side effects, generally resulting from the treatment, were attenuated (Raffaghello et al 2008).…”
Section: The Implication Of Dietary Restriction In Cancermentioning
confidence: 99%
“…The usefulness of STS has also been demonstrated for its attenuating properties on chemotherapy side effects. Indeed, its cardioprotective properties have been recently demonstrated during doxorubicin-based treatments (Dirks-Naylor et al 2014). In addition, a recent work on murine models revealed that following a prolonged fasting of 48-60 h prior to the administration of a high dose of etoposide, the side effects, generally resulting from the treatment, were attenuated (Raffaghello et al 2008).…”
Section: The Implication Of Dietary Restriction In Cancermentioning
confidence: 99%
“…Although calorie restriction mimetics are more practical in terms of sustainability, they are less accessible and cost ineffective. Fasting has been shown to exert beneficial effects on certain forms of cardiovascular diseases including age-related cardiac hypertrophy, myocardial ischemic injury, and coronary heart disease risk factors through diverse mechanisms including remodeling of mitochondrial networks, improvement of energy metabolism, reduction in signaling pathways related to survival such as insulin and insulin-like growth factor-1 signaling, decrease in mitochondrial oxidative stress, and enhancement of autophagic flux [97,98]. Recent studies suggest that fasting also conferred cardioprotection against DOX cardiotoxicity.…”
Section: Calorie Restriction and Fastingmentioning
confidence: 99%
“…Recent studies suggest that fasting also conferred cardioprotection against DOX cardiotoxicity. In animal models, short-term fasting ameliorates cardiac damage and cardiac dysfunction caused by DOX [98]. Alternate-day fasting, a type of intermittent fasting, is capable of mitigating DOX cardiotoxicity in mouse models of both acute and chronic DOX cardiotoxicity [30].…”
Section: Calorie Restriction and Fastingmentioning
confidence: 99%
“…Some studies have shown that STS induces cardioprotective effects against the injury caused by doxorubicin [56]. Moreover, Raffaghello et al [54] studied the effects of high-dose etoposide, a chemotherapeutic drug with a non-specific toxicity profile, in murine models undergone to fasting for 48-60 h, before the administration of a high-dose drug, and in a control group fed ad libitum.…”
Section: Dietary Restriction and Cancermentioning
confidence: 99%